Estado nutricional pré-gestacional e seus efeitos sobre o índice de massa corporal ao nascer: Coorte de Pré-Natal BRISA, São Luís - MA - Aráujo, Allanne Pereira (2015)
Objective. This study aims to examine the association maternal nutritional status on the size of the newborn. Methodology. Cohort study of 1365 pregnant women and their newborns, who attended the St. Louis BREEZE research - MA. Data were collected in 2010 and 2011 and were applied two questionnaires: one during the prenatal and the other was applied after delivery. The main explanatory variable was the body mass index (BMI) before pregnancy. This was classified as underweight/normal weight, overweight and obesity. From the theoretical assumptions, a theoretical model was proposed by directed acyclic graphs (DAGs English): 1) Total effects (ET) adjusted to economic class, education, marital status, maternal age and occupation, 2) direct effect (ED) adjusted to economic class, education, marital status, maternal age, occupation, alcohol and maternal smoking, high blood pressure during pregnancy and conducting prenatal care. Data were analyzed using multiple linear regression with BMI as the outcome of the newborn (NB). Results. The infants had birth average BMI of 13.4 ± 1.7 kg / m2.As for the pre-pregnancy BMI and BMI RN, association was observed in the model proposed by DAG to full effect. However, for the direct effects model, the type of delivery and the realization of prenatal were protective factors to the increase of the BMI RN: ED (p = <0,001; Coef .: 0,51; CI: 0,31 ; 0,70), ED (p: 0,027; Coef: -. 1,88; CI: -3,55, -0,21). However, schooling between 8-11 years of study in all models (ET and ED) were protective factor for increasing RN BMI. As for the pre-pregnancy BMI and BMI RN, is observed even as overweight (p: 0,008; Coef .: 0,08: CI: -0,06; 1,84) and obesity (p : 0,009; Coef .: 0,89; CI: -0,09, 1,86) pre-pregnancy increase the RN BMI also increases. Conclusion. Overweight and pre-gestational obesity appears to be associated with BMI RN such associations underscore the need for early prenatal care and continuing to pregnant women, which may contribute to reducing maternal and child mortality rates and other adverse developments that context.